The Relationship Between School Administrators’ Paternalistic Leadership Behaviors and Teachers’ Levels of Organizational Silence - Sönmez, Azmi; Cemaloğlu, Necati (Technium Social Sciences Journal, 2024)
The purpose of this study is to reveal the relationship between school administrators’ paternalistic leadership behaviors and teachers’ levels of organizational silence according to the views of the teachers participating in the study. Relational survey design was used in the research conducted using quantitative methods. The population of the study consists of 4836 teachers working in schools in a province of Turkey in the 2023-2024 academic year, and the sample consists of 526 teachers selected by simple random sampling method. Personal Information Form, School Principals’ Paternalistic Leadership Behaviors Scale and Organizational Silence Scale were used as data collection tools. SPSS 25 statistical package program was used to analyze the data. In the process of analyzing the first two sub-problems, arithmetic mean and standard deviation were analyzed for descriptive statistics. Correlation analysis was used to analyze the third sub-problem and regression analysis was used to analyze the fourth sub-problem. As a result of the research, it was seen that school administrators’ paternalistic leadership behaviors were generally at a low level and that philanthropic paternalistic leadership was dominant in the school. Teachers generally experience low levels of organizational silence, but when the sub-dimensions of organizational silence are examined, it is seen that the perception of managerial silence is the most dominant in the school. As the administrator behaviors related to the sub-dimensions of family atmosphere at school and philanthropy increase, teachers’ individual silence, organizational culture, colleagues, pressure groups and general organizational silence behaviors decrease. As the administrator behaviors related to the sub-dimensions of interventionism and inadequacy at school increase, teachers’ individual silence, organizational culture, colleagues, pressure groups and general organizational silence behaviors increase. As the administrator behaviors related to the sub-dimension of authoritarianism at school increase, teachers’ individual silence, administrative silence, organizational culture, colleagues, pressure groups and general organizational silence behaviors increase. It was seen that the benevolence, interventionism and finding inadequate sub-dimensions of paternalistic leadership were significant predictors of teachers’ organizational silence.